THE EFFECT OF STRAIN AND ALTITUDE ON BROILER PERFORMANCE - Rosidi, Rosidi; Suswoyo, Imam; Tugiyanti, Elly; Ismoyowati, Ismoyowati (ANIMAL PRODUCTION, 1999)
The research aimed to study the effect of strain and altitude on broiler performance, and to find out suitable strains kept either on low and high altitude. Low altitude was in Purwonegoro North Purwokerto (80 m asl) and high altitude was in Munggangsari Baturaden (755 m asl). The research was carried out since September 5th to December 5th, 1996 using 2x3 Factorial based on Completely Randomized Design. Factor I were land altitude (d) : low (d1) and high (d2). Factor II were broiler strains (g) : CP-707 (g1), AS-101 (g2) and Lohmann (g3). Data obtained were analyzed using F test continued  to Least Significant Difference Test. The research indicated that interaction between altitude and strains significantly affected  feed convertion and income over feed  and doc cost, while strain had significant effect on feed convertion. AS-101 and Lohmann strains  kept on low altitude had the highest final weight. The low altitude gave better feed convertion and income over feed and doc cost, whereas CP-707 strain had the best feed convertion. (Animal Production 1(2): 82-89 (1999) Key Words: strain, altitude, performance, broiler